Lymphocyte Level Profile Between Active and Inactive Systemic Lupus Erythematosus Patients Receiving Methylprednisolon Therapy - Rudi erwin Kurniawan (Jurnal FARMASIMED (JFM), 2025)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by chronic inflammation and excessive lymphocyte activation, requiring accurate monitoring of disease activity. This study aimed to analyze the differences in lymphocyte levels between active and inactive SLE patients receiving methylprednisolone therapy. The methodology involved measuring lymphocyte counts from patients’ venous blood samples, followed by classification based on the MEX-SLEDAI score as an indicator of disease activity. Data were then analyzed to determine significant differences between the two groups. The results demonstrated that patients with active SLE had significantly lower lymphocyte counts (mean 838.35/μL) compared to inactive patients (mean 1957.65/μL). These findings indicate that a decrease in lymphocyte levels is closely associated with higher disease activity, suggesting that lymphocyte count may serve as a potential indicator of SLE activity. In conclusion, lymphocyte levels can be considered a useful parameter for assessing disease activity in SLE patients undergoing methylprednisolone therapy. This study provides valuable insight for clinical diagnosis and disease activity monitoring. Times New Roman 9 pt and single space. The abstract should contain the background, objectives, methodology, results, and conclusions. The abstract should contain background, objectives, methodology, results, and conclusions and be written in each opening paragraph. The abstract should not contain tables/images without including a citation. The use of abbreviations should be minimum except for units. Objectives and methodology are arranged in the form of past tense, while the results and conclusions in the form of simple present tense.